The Effectiveness of Blended Learning as an Instructional Model in Vocational High School - Iga Setia Utami (Journal of Educational Science and Technology (EST), 2018)
The purpose of this research was to evaluate the effectiveness of blended learning as an instructional model in vocational high school. The method used was a Quasy Experimental with Nonequivalent Control Group Design. Students are divided into two groups: an experimental group is a group of students that use blended learning model and control group with conventional learning models. Data were collected by achievement test in the form of an objective matter than do the test requirements analysis in the form of normality test, homogeneity test, and t-test. The results showed that 1) the results of student learning experimental group was higher than the results of student learning control group, 2) improving student learning outcomes in the experimental group was higher than the control group, 3) The completeness of student learning outcomes after using blended learning models reach the set limit. Based on the findings of the study, concluded that the blended learning model is effective to be used as an instructional model